Total Synthesis of Cryptocaryol A via Enantioselective Iridium Catalyzed Alcohol C-H Allylation() - Perez, Felix (Angew Chem Int Ed Engl, 2016)
The polyketide natural product Cryptocaryol A is prepared in 8 steps via iridium catalyzed enantioselective diol double C-H allylation, which directly generates an acetate-based triketide stereodiad. In 4 previously reported total syntheses, 17-28 steps were required. [Image: see text]